Sexual Dimorphism in Colon Cancer - Abancens, Maria; Bustos, Viviana; Harvey, Harry; McBryan, Jean; Harvey, Brian J. (Frontiers in Oncology, 2020)
A higher incidence of colorectal cancer (CRC) is found in males compared to females. Young women (18-44 years) with CRC have a better survival outcome compared to men of the same age or compared to older women (over 50 years), indicating a global incidence of sexual dimorphism in CRC rates and survival. This suggests a protective role for the sex steroid hormone estrogen in CRC development. Key proliferative pathways in CRC tumorigenesis exhibit sexual dimorphism which confer better survival in females through estrogen regulated genes and cell signaling. Estrogen regulates the activity of a class of Kv channels (KCNQ1:KCNE3) which control fundamental ion transport functions of the colon as well as epithelial-to-mesenchymal transition through bi-directional interactions with the Wnt/B-catenin signalling pathway. Estrogen also modulates CRC proliferative responses in hypoxia via the novel membrane estrogen receptor GPER and HIF-1A and VEGF signaling. Here we critically review recent clinical and molecular insights into sexual dimorphism of CRC biology modulated by the tumor microenvironment, estrogen, Wnt/B-catenin signalling, ion channels, and X-linked genes.